2022
DOI: 10.1039/d1tc04194k
|View full text |Cite
|
Sign up to set email alerts
|

Color-tuning Pt(ii) complexes for natural-light electrophosphorescence

Abstract: Efficient and durable OLEDs of cyan, greenish yellow, yellow and white colors were fabricated in simple structures with Pt–Cpy bonded complexes, giving state-of-the-art tuning the color of electroluminescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Pt­(II) complexes of tetradentate ligands are fused with several consecutive platinacycles, , including one of which is in the form of 5–6–6, which are highly twisty and difficulty to form dimers or multimers. , The structure has been demonstrated to be a good candidate for the blue PhOLEDs. , In addition, upon introducing nitrogen into the phenyl ring to form the Pt-C Py (py is pyridinyl group) coordination bond, the Pt­(II) complexes with a pyrazolyl-pyridinyl (pzpy) segment in the ligand exhibit increased intermolecular attraction due to π–π interactions . However, to a certain extent, in those complexes with 5–6–6 fused platinacycles, , the feasibility of forming excimer-based emission in doping matrixes highly depends on their molecular distortions. , (Chart ) As a result, we found that the highly twisted structures with a large band gap are superior for blue phosphorescent emitters, whereas the structures with less distortions are more favorable for broad spectral emission. On the other hand, Pt­(II) complex in 5-6-5 metallocycles has less steric hindering effect, meaning it is highly flat along the molecular plane and easier to access for the excimer-based emission .…”
Section: Introductionmentioning
confidence: 99%
“…Pt­(II) complexes of tetradentate ligands are fused with several consecutive platinacycles, , including one of which is in the form of 5–6–6, which are highly twisty and difficulty to form dimers or multimers. , The structure has been demonstrated to be a good candidate for the blue PhOLEDs. , In addition, upon introducing nitrogen into the phenyl ring to form the Pt-C Py (py is pyridinyl group) coordination bond, the Pt­(II) complexes with a pyrazolyl-pyridinyl (pzpy) segment in the ligand exhibit increased intermolecular attraction due to π–π interactions . However, to a certain extent, in those complexes with 5–6–6 fused platinacycles, , the feasibility of forming excimer-based emission in doping matrixes highly depends on their molecular distortions. , (Chart ) As a result, we found that the highly twisted structures with a large band gap are superior for blue phosphorescent emitters, whereas the structures with less distortions are more favorable for broad spectral emission. On the other hand, Pt­(II) complex in 5-6-5 metallocycles has less steric hindering effect, meaning it is highly flat along the molecular plane and easier to access for the excimer-based emission .…”
Section: Introductionmentioning
confidence: 99%
“…The basic components of EAF slag are CaO, FeO, Al 2 O 3 , SiO 2 , MgO, and MnO. Surface tension has been obtained from the experiment results of Wu et al and Xuan et al [ 11,25 ] The surface tensions and densities of the slag components are in a function of temperature and they have been presented in Table 2 .…”
Section: Numerical Modelmentioning
confidence: 99%
“…[ 10 ] Wu, Albertsson, and Du did a series of experiments about foaming phenomenon and developed a mathematical model to illustrate the relationship of foaming height and slag properties. [ 11 ] These researches were focused on the calculation of slag foaming height.…”
Section: Introductionmentioning
confidence: 99%
“…Organic luminescent materials in the deep-red to near-infrared region have become a hotspot in displays and solid lighting due to their broad applications in night vision displays, information security equipment, photodynamic therapy and organic lightemitting diodes (OLEDs). [1][2][3][4][5][6][7][8][9][10] In the past few decades, a series of highly efficient phosphorescent complexes of iridium (Ir), [11][12][13][14] osmium (Os) [15][16][17][18] and platinum (Pt) [19][20][21][22][23][24][25][26] have been developed by virtue of the heavy atom effect with an intrinsic 100% internal quantum efficiency. However, due to the limitations of the energy gap law and quenching effect in the aggregation state, there are still great difficulties in innovatively developing long-wavelength and high-efficiency near-infrared (NIR) luminescent materials.…”
Section: Introductionmentioning
confidence: 99%